Examining the financial performance of agricultural cooperatives in the USA. Issue 2 (8th January 2019) - Pokharel, Krishna Prasad; Regmi, Madhav; Featherstone, Allen M.; Archer, David W.
Abstract : Purpose: The purpose of this paper is to identify financial stress and the causes of financial stress for agricultural cooperatives and provide management recommendations to stakeholders including cooperatives' managers, boards of directors and lenders. Design/methodology/approach: This research used the geometric mean of the real rate of return on equity to identify financially stressed agricultural cooperatives. The real rate of return on equity allows the allocation of total financial stress among the return on assets, leverage and interest rate issues. Findings: This study found that financially non-stressed agricultural cooperatives had a higher rate of return on equity and rate of return on assets, but lower leverage ratios and interest rates than stressed agricultural cooperatives. Further, non-stressed cooperatives had higher total assets and sales compared to stressed cooperatives. This suggests that smaller cooperatives are more likely to face financial stress than larger cooperatives. The decomposition of the financial problem showed that a substantial percentage of financial stress was correlated with a low return on assets or profitability. A smaller percentage of financial stress was due to financing decisions. Originality/value: This study provides value by measuring the impact of profitability, leverage and interest rate on the financial performance of agricultural cooperatives. Results showed that a substantial proportion of financial stress was associated with a low return on assets. This indicates that profitability is a problem for agricultural cooperatives. This study also examines profitability during a period of volatile returns in production agriculture.